2016
DOI: 10.1007/s12350-015-0392-0
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Ventricular Arrhythmias: Current Role of Imaging in Diagnosis and Risk Assessment

Abstract: Sudden cardiac arrest continues to be a major cause of death from cardiovascular disease but our ability to predict patients at the highest risk of developing lethal ventricular arrhythmias remains limited. Left ventricular ejection fraction is inversely related to the risk of sudden death but has a low sensitivity and specificity for the population at risk. Nevertheless, it continues to be the main variable considered in identifying patients most likely to benefit from implantable defibrillators to prevent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…If this excess norepinephrine is present in areas containing viable myocardium, the myocytes may be subject to denervation hypersensitivity, which in turn may predispose to catecholamine-mediated arrhythmias. Studies using these agents found that patients exhibiting greater degrees of myocardial denervation (less uptake of the tracer) have higher mortality and more arrhythmic events (101)(102)(103). This technique for SCD risk stratification remains in the early stages, and significantly more data are needed before it can be incorporated into routine clinical practice.…”
Section: Imaging Techniques To Identify Denervated Myocardiummentioning
confidence: 99%
“…If this excess norepinephrine is present in areas containing viable myocardium, the myocytes may be subject to denervation hypersensitivity, which in turn may predispose to catecholamine-mediated arrhythmias. Studies using these agents found that patients exhibiting greater degrees of myocardial denervation (less uptake of the tracer) have higher mortality and more arrhythmic events (101)(102)(103). This technique for SCD risk stratification remains in the early stages, and significantly more data are needed before it can be incorporated into routine clinical practice.…”
Section: Imaging Techniques To Identify Denervated Myocardiummentioning
confidence: 99%
“…Use of a risk prediction model will understandably have a low sensitivity for predicting arrhythmic events; however, it offers a high specificity and a high negative predictive value to identify those at the lowest risk. This has been suggested in multiple prior studies utilizing imaging and biomarker-based risk prediction tools to predict arrhythmic events in various HF populations, 16 including a gated SPECT-based model of LV ejection fraction, myocardial scar. and dyssynchrony.…”
Section: See Related Article Pp 1282-1288mentioning
confidence: 99%